2009
DOI: 10.1002/app.29791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycidyl methacrylate treatment of empty fruit bunch (EFB) on the properties of ultra‐violet radiation cured EFB‐unsaturated polyester composite

Abstract: In this study, biofiber composites cured by ultra-violet, were produced using pulp made from empty fruit bunch (EFB) as the reinforcing agent and unsaturated polyester as the matrix. The conversion of EFB fibers into pulp was carried out using organosolv pulping process. The EFB pulp was then chemically treated with glycidyl methacrylate (GMA) to different percentage of weight percent gain and the composites were made with different percentages of pulp loading. Results showed that the Kappa number of EFB decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A number of researchers reported work done on EFB/polymer composites. [10][11][12][13][14][15][16][17] Studies on EFB fibre-reinforced polypropylene (PP) composites showed that the tensile strength of the composites decreased, while the tensile modulus increased with increasing EFB filler loading. 10,13 In the case of glycidyl methacrylate treatment of EFB and ultraviolet radiation curing of EFB-unsaturated polyester composites, however, both the tensile strength and modulus increased noticeably with increasing EFB content.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers reported work done on EFB/polymer composites. [10][11][12][13][14][15][16][17] Studies on EFB fibre-reinforced polypropylene (PP) composites showed that the tensile strength of the composites decreased, while the tensile modulus increased with increasing EFB filler loading. 10,13 In the case of glycidyl methacrylate treatment of EFB and ultraviolet radiation curing of EFB-unsaturated polyester composites, however, both the tensile strength and modulus increased noticeably with increasing EFB content.…”
Section: Introductionmentioning
confidence: 99%
“…By the way, this short curing time should also be beneficial to reduce the emission of styrene usually used as reactive diluent and which presents safety issues. However, only few works reported the use of light for such purpose . For example, ultraviolet (UV)‐curing was used to replace the thermally cured resins for repairing damaged reinforced concrete .…”
Section: Introductionmentioning
confidence: 99%
“…However, only few works reported the use of light for such purpose. [1][2][3][4][5][6][7][8][9] For example, ultraviolet (UV)-curing was used to replace the thermally cured resins for repairing damaged reinforced concrete. 3,10,11 The UV-cured fiber-reinforced polymer was also developed for pipes repairing.…”
Section: Introductionmentioning
confidence: 99%
“…The oil palm industry in Malaysia generates large quantities of biomass. Our research team present a variety of publications that related to oil palm industry using curing technology [8][9][10][11][12][13][14][15][16][17][18]. Most of these investigations show that various products can be produced from the by-products of the palm oil industry, such as oil palm component plastic composite [8], oil palm componentrubber composite [9], sheet moulding compound [10] and pulp-paper [11].…”
Section: Introductionmentioning
confidence: 99%